أثر استخدام مواد آمنة بيئياً لتنعيم الحرير الصناعي بدون اختزال الوزن على الخواص الطبيعية والجدوى الاقتصادية - مأمون، أمل عبدالسميع; الجوهري، رشا عباس محمد متولى (جامعة المنصورة - كلية التربية النوعية, 2013)
Functional work quality for every kind of clothes depends on its natural and mechanical properties which are suitable to this function and these properties are changing according to the change in structure combination elements of clothes and also according to different methods used in its preparation to cope up with clothes needs. This is the research matter for measuring the effect of environmental safety substances usage in softening artificial silk and the improvement of its properties without weight reduction and the effect of that on its natural properties.
Keywords: صناعة الغزل والنسيج -- الحرير الصناعي -- صناعة الملابس الجاهزة -- الجدوى الاقتصادية